The Rastafari movement: a North American and Caribbean perspective - Barnett, Michael A. (Routledge, 2017)
Pan-Africanism, Black Nationalism, Ethiopianism and Rastafari : A Historical Perspective -- General Overview of the Organizational Structure of the Rastafari Movement -- The Different Mansions of the Rastafari Movement -- Gender Dynamics Within the Rastafari Movement -- Important Concepts and Symbols for the Rastafari Movement -- The Globalization of the Rastafari Movement -- Out in the Field -- A Comparison between the Rastafari Movement and other Black Theological Movements such as the Nation of Islam and the Black Hebrew Israelites -- Reflections on the Current Status of the Rastafari Movement.